Medicinal plants for treatment of diabetes mellitus - Shukia, R. (Springer India, 2000)
Many plants have been used for the treatment of diabetes mellitus in Indian system of medicine and in other ancient systems of the world. Out of these only a few have been evaluated as per modern system of medicine. From many such plants only extracts have been prepared and their usefulness evaluated in experimental diabetes in animals. In some plants likeAllium cepa, Allium sativum, Ficus bengalensis, Gymnema sylvestre, Pterocarpus marsupium etc. active hypoglycemic principles have been isolated and their mechanism of action studied. Most of them seem to act directly on pancreas (pancreatic effect) and stimulate insulin level in blood. Some have extra pancreatic effect also by acting directly on tissues like liver, muscle etc. and alter favourably the activities of the regulatory enzymes of glycolysis, gluconeogenesis and other pathways. Since the plant products have less side effects, they have the potential as good hypoglycemic drugs. They may also provide clues for the development of new and better oral drugs for diabetes.